(3GdeaJGM deG CZdb ef aQGM GdCQhGMs - (3LeGd GdOjf Hf YeQ Hf MSfi GdTGaYjs; (3UGMH GdeQGM , CMeO Hf Ydj Hf eSYhO, MSGe GdOjf CHh GdaVGFd,J (B700 (3g` s
(3ChdgG (B:s
(3gPG JYdjb ef cJGH eQGM GdCQhGM s
(3BNQgG (B:s
(3YOe EYdGd GdYjf GdJGHYI fMh WhjG hWGhjGf s
(3eQGM GdCQhGM GfXQ cTa GdXfhf L (B2 (3U`(B1651s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas